World poverty : new policies to defeat an old enemy - Townsend, Peter, 1928-2009; Gordon, David, 1959- (The Policy Press, 2002)
The study, when published in 2002, received coverage across the globe from Brazil to Greece and attracted the support of the then High Commissioner for Human Rights, Mary Robinson. Anyone interested in understanding, campaigning or simply debating the issues facing policy makers today will find this book a rich and compelling resource.